The effect of COVID-19 on completed suicide rate in Iran: an Interrupted Time Series study (ITS) - Nouhi Siahroudi, Azadeh; Hashemi Nazari, Seyed Saeed; Namdari, Mahshid; Panahi, Mohammad Hossein; Mahdavi, Seyed Amirhosein; Khademi, Ali (Frontiers in Public Health, 2025)
BackgroundSuicide represents a critical public health concern and one of the most devastating forms of death. Based on a report from the World Health Organization, around 700,000 deaths by suicide occur globally each year. In 2019, the worldwide suicide mortality rate was 9.0 per 100,000 people, while in Iran, this rate has been reported to be an average of 5.2 per 100,000. Suicide is influenced by various factors spanning individual, relational, community, and social domains, all of which may elevate the risk of suicide and related death. One significant factor potentially impacting this issue was the COVID-19 pandemic, which may have affected these trends by disrupting individuals’ social interactions and gatherings. To explore this further, the present study was carried out to investigate the impact of the COVID-19 pandemic on the changes in suicide rates leading to death in Iran.MethodsThis study was designed using an Interrupted Time Series approach combined with negative binomial regression. Seasonal variations were adjusted for using the harmonic method. The research sample comprised 63,514 suicide-related deaths recorded between April 20, 2009, and March 20, 2023. Suicide mortality data were sourced from the National Legal Medicine Organization, while population statistics were obtained from the official website of the Statistical Center of Iran. The study analyzed trends in suicide incidence both prior to and during the COVID-19 pandemic. The period used to evaluate pandemic-related changes in Iran began in May 2020, following the World Health Organization’s declaration of COVID-19 as a global public health emergency. Descriptive analyses were performed using Stata software, and trend assessments through the Interrupted Time Series (ITS) method were conducted using R software and the “lmtest” statistical package.ResultsThe changes in the incidence of suicide during the study increased by 1.003 monthly (p < 0.001). This rate increased by 1.1 (p < 0.001) compared to the times before the onset of the pandemic after entering the effect of the COVID-19 pandemic in the model. When the interaction effect of time with the COVID-19 pandemic was added to the base model, no significant relationship was observed.ConclusionBefore the COVID-19 pandemic, suicides in Iran had a proportional increasing trend. However, three months after the pandemic, an increasing trend in the level of suicide deaths was observed. Most likely, the COVID-19 pandemic phenomenon had an impact on the occurrence of suicide.